SSL Based Cryptography Data Management in Private Cloud Computing - Meenakshi, D; Devi, V. Karthika (International Journal of Computer Sciences and Engineering, 2019)
As a personal or business cloud computing user can processing their accumulated information on the 'cloud', via an Internet connection. The main attitude following this form is for providing, processing, storing “as a service.” Technologies such as cluster have all aimed at providing permission to accessing huge amount of information on entirely implicit way by combine the resources and recommending distinct sight of the structure. Network security is goings-on which were modelled for preventing our data while used on the network. It was included on both the technologies of hardware as well as software. Network security technology achieved variety of its targets such as coercions and prevents them from stabbing or extending on the network in this paper SSL handled the data in private cloud computing.